A contribuição dos jogos de empresa para o estudo da análise de investimento - Bortoluzzi, Viviane Campanhola (2010)
This paper presents a method of investment analysis to be applied in the Metaltec business game, aiming to facilitate the learning of the main methods of investment analysis. Business games contribute to this study because they bring the player closer to the reality, enhancing learning in management fields such as finance, production and sales. The work was divided into two studies. The first study examines whether companies in Santa Maria Rio Grande do Sul, Brazil perform investment analysis when purchasing equipment. The research was carried out with micro and small businesses in Santa Maria through a semi-structured questionnaire. From this analysis we could conclude that companies do not make investment analysis, but calculate whether the investment is viable or not only based on the increased demand. The second study presents the methodology of investment analysis for the business games. The research was performed in the Graduation Program in the Production Engineering with the groups of the second term of 2008 and second term of 2009. The application of 2008 showed more similar results because their players were from areas related to production engineering while the implementation of 2009 brought a number of discrepancies during the game because the players had different academic backgrounds. However, even with the difficulties players had, business games contributed to their learning management. Moreover, the study of methods of investment analysis in the game business contributed to the learning of Engineering Economy, facilitating its understanding since students worked within a company and not with decontextualized problems.